(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2021)
This article provides an overview of HBO television series in Hungary and Romania, highlighting their relation to film traditions in each country. While it might seem surprising that HBO helped create original series in countries without a long-standing tradition in quality television, the roots for this ‘wave’ of Eastern European shows can actually be traced in local film production tradition. For these shows, HBO has worked to make regional voices heard internationally. These two Eastern European neighbours belong to the same categories in terms of cinema and television production in that they represent small markets with potential for development under the support of Western media. Yet this article shows how cultural differences surface when comparing these two countries’ filmic traditions, authorial perspectives, international recognition of professionals, and domestic audiences. In Hungary, prestigious directors, as well as new television professionals and ‘outsiders’ from other fields, play significant roles in HBO projects. Together, they develop a relatively wide range of genres that target a broad spectrum of audience demographics. In the case of Romania, there exists a certain continuity with New Romanian Cinema in the HBO series. The Romanian productions attempt to attract larger numbers among domestic viewers in addition to international audiences. The emergent quality television in both countries demonstrates a reliance on the small cinema tradition, while capitalizing on the success of certain academic directions and the success independent film enjoyed in Europe. Given the lack of cooperation in Eastern Europe across numerous cultural and creative industries following 1989, this article examines how HBO acts as a catalyst for Hungarian and Romanian creativity. By bringing together local resources and using its legitimacy as a major player in international television, HBO empowers local professionals to upgrade the quality of their televised content.